Old Maid No More - Donna Davis (EDIS)
“Twenty years ago, women were being warned that, according to demographic research, if they didn’t marry by the time they were in their early twenties, they would likely live out their lives unwed. As a child, I was even told that “those” women became “old maids,” and I feared a similar fate. Fast-forward to 2006, and the news is quite different.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, March 2012.